ANALYSIS OF FINANCIAL LITERACY AND DIGITAL LITERACY STUDIES ON BUSINESS SUSTAINABILITY IN FOOD MSMES: THE ROLE OF DIGITAL PAYMENT MEDIATION - Fania Agustina; Edwin Zusrony; Ratnaningrum; Titik Rianawati; Olivia Rahmala Ihwan (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to clarify whether Digital Payment mediates the relationship between financial literacy and digital literacy on business sustainability. This study discusses the study of financial literacy and digital literacy in MSMEs. This study used a quantitative method involving a sample of 50 food retail MSMEs in Semarang Regency, Central Java Province. The sampling technique used a purposive sampling method and was assessed using a questionnaire instrument with a 1-5 Likert scale. The results show that digital literacy has a significant influence on digital payment. The digital payment variable also has a significant influence on business sustainability. Furthermore, the financial literacy variable has a significant influence on business sustainability. Meanwhile, the financial literacy variable does not have a significant influence on digital payment. Meanwhile, this study also revealed that the digital payment variable does not mediate the relationship between financial literacy and digital literacy on business sustainability. The results of this research are expected to provide a comprehensive picture for MSMEs regarding the impact of financial literacy and digital literacy on business sustainability mediated by digital payment.